Improving CBR management at provincial level - Pierdomenico, Lorenzo ([Ha Noi], 2008)
The document has been designed for staff at provincial and district levels, responsible for managing and co-coordinating Community-Based Rehabilitation (CBR) activities. The aim of the document is to offer practical advices and baseline management principles, tools and procedure to be implemented, in order to strengthen the management of the CBR program in their area.